Cohesive Devices In English-Language Indonesian Online News: A Discourse Analysis Of The Jakarta Post Articles On The Iran Conflict - Putra Puadi; Sukri Adani (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study examines the use of cohesive devices in English-language opinion articles published in The Jakarta Post, Indonesia's premier English-language newspaper. Drawing on Halliday and Hasan's (1976) framework of cohesion in English, the research employs quantitative content analysis to investigate the frequency, distribution, and utilization of cohesive devices across a corpus of ten opinion articles concerning the Iran conflict, published between March and April 2026. The analysis reveals that reference (29.07%, n = 91) and lexical cohesion (29.07%, n = 91) constitute the dominant cohesive strategies, followed by conjunction (19.49%, n = 61), substitution (12.78%, n = 40), and ellipsis (9.58%, n = 30). Within the reference category, anaphoric reference emerges as the most frequently employed sub-type (15.97%), while repetition emerged as the dominant subtype of lexical cohesion. The distribution of cohesive devices indicates a clear preference for referential and lexical strategies in maintaining continuity across the selected articles. These findings contribute to discourse analysis by providing empirical evidence of cohesion patterns in Indonesian English-language journalism and offer pedagogical implications for EAP and ESP instruction.